The Effect of using E-Booklet Media on Increasing the Knowledge of Primigravida Mothers about Breastfeeding Techniques and Newborn Umbilical Cord Care - Hasrida Hasrida; Melisa Rian Sari; Silvia Nada (GLOBAL HEALTH SCIENCE GROUP, 2025)
Primigravida mothers often lack sufficient knowledge about newborn care, including umbilical cord care and breastfeeding techniques. Better education and support from healthcare professionals are essential to enhance their knowledge and skills in infant care. Effective training and counseling can help primigravida mothers feel more confident and competent in caring for their children. This study aims to determine the effect of e-booklet media on the knowledge of primigravida mothers regarding breastfeeding techniques and umbilical cord care in the service area of the Pamandegan Health Center and Midwife Clinic. This research uses a quantitative method with a pre-experimental design and a one-group pretest-posttest research design. The sample size in this study was 68 respondents, selected using total sampling, and all respondents received the intervention for 1 month. The measurement tool used in this study was a questionnaire that had undergone normality and validity tests. Normality was tested using the Shapiro-Wilk test, and data analysis was conducted using univariate analysis and bivariate analysis with the Wilcoxon test. The hypothesis test results showed a p-value = 0.000 < 0.05, indicating that the use of e-booklet media significantly affected the knowledge of primigravida mothers regarding breastfeeding techniques and umbilical cord care. It is crucial for primigravida mothers to improve their knowledge in these two aspects as it can greatly impact their ability to care for their babies effectively.